The miracle club [videorecording (DVD)] - Smallhorne, Jimmy; Prager, Timothy; Maurer, Joshua; Linney, Laura; Bates, Kathy, 1948-; Smith, Maggie, 1934-; O'Casey, Agnes, 1995 or 1996-; O'Halloran, Mark; McKenna, Mark, 1996-; Buggy, Niall, 1948-; Doupe, Hazel, 2002-; Rea, Stephen (Sony Pictures Home Entertainment, 2023)
Set in 1967, a heartwarming film that follows the story of three generations of close friends, Lily, Eileen, and Dolly of Ballygar, a hard-knocks community in Dublin, who have one tantalizing dream: to win a pilgrimage to the sacred French town of Lourdes, that place of miracles that draws millions of visitors each year. When the chance to win presents itself, the women seize it. However, just before their trip, their old friend Chrissie arrives in Ballygar for her mother's funeral, dampening their good mood and well-laid plans. The women secure tickets and set out on the journey that they hope will change their lives, with Chrissie, a skeptical traveler, joining in place of her mother. The glamor and sophistication of Chrissie, who has just returned from a nearly 40-year exile in the United States, are not her only distancing traits: Old wounds are reopened along the way, forcing the women to confront their pasts even as they travel in search of a miracle. Their shared traumas can only be healed by the curative power of love and friendship.